A 3.1-5.2GHz, Energy-Efficient Single Antenna, Cancellation-Free, Bitwise Time-Division Duplex Transceiver for High Channel Count Optogenetic Neural Interface - Lin, Yu-Ju; Song, Hyunsoo; Oh, Sungjin; Voroslakos, Mihaly; Kim, Kanghwan; Chen, Xing; Wentzloff, David D.; Buzsaki, Gyorgy; Park, Sung-Yun; Yoon, Euisik (Institute of Electrical and Electronics Engineers, 2022)
We report an energy-efficient, cancellation-free, bit-wise time-division duplex (B-TDD) transceiver (TRX) for real-time closed-loop control of high channel count neural interfaces. The proposed B-TDD architecture consists of a duty-cycled ultra-wide band (UWB) transmitter (3.1-5 GHz) and a switching U-NII band (5.2 GHz) receiver. An energy-efficient duplex is realized in a single antenna without power-hungry self-interference cancellation circuits which are prevalently used in the conventional full-duplex, single antenna transceivers. To suppress the interference between up- and down-links and enhance the isolation between the two, we devised a fast-switching scheme in a low noise amplifier and used 5x oversampling with a built-in winner-take-all voting in the receiver. The B-TDD transceiver was fabricated in 65 nm CMOS RF process, achieving low energy consumption of 0.32 nJ/b at 10 Mbps in the receiver and 9.7 pJ/b at 200 Mbps in the transmitter, respectively. For validation, the B-TDD TRX has been integrated with a mu LED optoelectrode and a custom analog frontend integrated circuit in a prototype wireless bidirectional neural interface system. Successful in-vivo operation for simultaneously recording broadband neural signals and optical stimulation was demonstrated in a transgenic rodent.